Risk of loss to follow-up among tuberculosis patients in South Korea: whom should we focus on? - Kim, Hyung Woo; Min, Jinsoo; Ko, Yousang; Oh, Jee Youn; Jeong, Yun-Jeong; Lee, Eun Hye; Yang, Bumhee; Koo, Hyeon-Kyoung; Lee, Sung-Soon; Park, Jae Seuk; Park, Kwang Joo; Chang, Jung Hyun; et al. (Frontiers in Public Health, 2023)
Introduction In South Korea, public-private mix (PPM) has been a key strategy in national tuberculosis (TB) control program. This study aimed to identify rate of loss to follow-up (LTFU) among TB patients in nationwide PPM institutions and their risk factors. Methods A nationwide prospective observational study including drug susceptible TB patients diagnosed from the 1st day to the 10th day of every month between July 2018 and December 2020 in PPM institutions was designed. Multivariable survival models in which death and failure were designated as events with competing risk were used to investigate risk factors for LTFU. Results A total of 14,942 patients were included. Of them, 356 (2.4%) had an LTFU. Risk factors for LTFU were: underweight patients (adjusted hazard ratio (aHR): 1.47, 95% CI: 1.12–1.92), patients living alone (aHR: 1.43, 95% CI: 1.16–1.76), heavy drinkers (aHR: 1.67, 95% CI: 1.16–2.39), those with malignancy (aHR: 1.49, 95% CI: 1.07–2.05), foreigners (aHR: 5.96, 95% CI: 4.51–7.89), and those with previous TB history reported as an unfavorable outcome (aHR: 4.43, 95% CI: 2.77–7.08). Effect of age on LTFU was not significant. Brief interruption of anti-TB treatment (less than two months) in current session was associated with subsequent LTFU [adjusted odds ratio: 13.09 (10.29–16.66)]. Conclusion Identifying vulnerability of patients such as living alone, being heavy alcoholics, being foreigners or having previous TB history reported as an unfavorable outcome is required. Thorough case management for these vulnerable groups could be feasible with collaboration between public and private sectors.